Structural Principles or Frequency of Use? An ERP Experiment on the Learnability of Consonant Clusters - Wiese, Richard; Orzechowska, Paula; Alday, Phillip M.; Ulbrich, Christiane (Frontiers in Psychology, 2017)
Phonological knowledge of a language involves knowledge about which segments can be combined under what conditions. Languages vary in the quantity and quality of licensed combinations, in particular sequences of consonants, with Polish being a language with a large inventory of such combinations. The present paper reports on a two-session experiment in which Polish-speaking adult participants learned nonce words with final consonant clusters. The aim was to study the role of two factors which potentially play a role in the learning of phonotactic structures: the phonological principle of sonority (ordering sound segments within the syllable according to their inherent loudness) and the (non-)existence as a usage-based phenomenon. EEG responses in two different time windows (adversely to behavioural responses) show linguistic processing by native speakers of Polish to be sensitive to both distinctions, in spite of the fact that Polish is rich in sonority-violating clusters. In particular, a general learning effect in terms of an N400 effect was found which was demonstrated to be different for sonority-obeying clusters than for sonority-violating clusters. Furthermore, significant interactions of formedness and session, and of existence and session, demonstrate that both factors, the sonority principle and the frequency pattern, play a role in the learning process.